2002
DOI: 10.1037/0022-006x.70.3.590
|View full text |Cite
|
Sign up to set email alerts
|

Biobehavioral outcomes following psychological interventions for cancer patients.

Abstract: Psychological interventions for adult cancer patients have primarily focused on reducing stress and enhancing quality of life. However, there has been expanded focus on biobehavioral outcomeshealth behaviors, compliance, biologic responses, and disease outcomes-consistent with the Biobehavioral Model of cancer stress and disease course. The author reviewed this expanded focus in quasi-experimental and experimental studies of psychological interventions, provided methodologic detail, summarized findings, and hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
132
6
10

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 188 publications
(150 citation statements)
references
References 191 publications
(317 reference statements)
2
132
6
10
Order By: Relevance
“…If left untreated, this early stress contributes to a consistently low quality of life, slower recovery, and less meaning in patients' lives [1][2][3][4]. The needs of patients go unaddressed [5] despite the fact that 30 years of randomized clinical trials (RCTs) designed for cancer patients show that we can consistently reduce patients' stress and enhance their moods [6][7][8][9], coping [7,10], and quality of life [6]. Dissemination is defined as the targeted distribution of information and intervention materials to a specific public health or clinical practice audience to spread knowledge of the evidence-based intervention [11].…”
Section: Introductionmentioning
confidence: 99%
“…If left untreated, this early stress contributes to a consistently low quality of life, slower recovery, and less meaning in patients' lives [1][2][3][4]. The needs of patients go unaddressed [5] despite the fact that 30 years of randomized clinical trials (RCTs) designed for cancer patients show that we can consistently reduce patients' stress and enhance their moods [6][7][8][9], coping [7,10], and quality of life [6]. Dissemination is defined as the targeted distribution of information and intervention materials to a specific public health or clinical practice audience to spread knowledge of the evidence-based intervention [11].…”
Section: Introductionmentioning
confidence: 99%
“…14 In addition, psychological interventions focusing on cancer-related stress and QOL could help narrow the racial disparities in PCa management. 15 To better understand what is known about the management of PCa for minorities, we conducted a systematic review of the literature summarizing interventions to improve informed decision making about PCa detection among screening-eligible minorities, and QOL among minority PCa survivors.…”
Section: Introductionmentioning
confidence: 99%
“…Reviews of separate physical interventions (Courneya & Friedenreich 1999;Irwin & Ainsworth 2004;Oldervoll et al 2004;Schwartz 2004) and psychosocial interventions (Fawzy et al 1995;Meyer & Mark 1995;Andersen 2002) for cancer patients show benefits on physical and psychosocial functioning, and other quality of life domains. Several combined cancer rehabilitation interventions (Berglund et al 1994;Mock et al 1994;Courneya et al 2003;Van Weert et al 2004, 2005Korstjens et al 2006) showed beneficial quantitative outcomes.…”
Section: Introductionmentioning
confidence: 99%